EFFECTS OF RESISTANCE TRAINING ON THE BLOOD LIPID VARIABLES OF YOUNG ADULTS - Ajayi-Vincent, O.B.; Adesina, M.O. (European Scientific Journal, ESJ, 2013)
﻿﻿﻿This study investigated the effects of a-12 week resistance training regimen on the blood lipid variables of young adults in Ekiti state, Nigeria. It was hypothesized that there would be no significant effect of a 12- week resistance training program on the lipid profile of young adults in Ekiti state. Sixty young college students were randomly assigned to two groups (resistance training and control). Pre-test, mid-test and post-test measurements were taken and analyzed using mean, standard deviation and Analysis of Covariance (ANCOVA) statistics at 0.05 level of significance. Following significant differences, the Multiple Classification Analysis (MCA) was computed. These statistical analyses revealed significant differences in the lipid profiles of the resistance training group following the 12-week training program; with a decrease in total cholesterol from 4.88 + 0.85 to 3.78 + 0.63 mmol/l, triglycerides from 0.64 + 0.16 to 0.57 + 0.15 mmol/l and Low density lipoprotein (LDL) from 2.74 + 0.52 to 2.04 + 0.52 mmol/l. High density lipoprotein (HDL) increased from 1.63 + 0.27 to 2.00 + 0.37 mmol/l in the training group and no appreciable changes in the control group. The study concluded that training regimen of this nature is capable of lowering LDL and raising HDL cholesterol levels in healthy young adults and can be a useful adjunct to therapeutic measures for prevention of coronary heart diseases (CHDs.)